2014
DOI: 10.1159/000369462
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injuries Prone to Infectious Risks amongst Healthcare Personnel in Kuwait: A Retrospective Study

Abstract: Objective: The study aimed at determining the prevalence of incident occupational exposure to blood and other potentially infectious materials (OPIM) among healthcare personnel (HCP) during 2010 and at evaluating the factors associated with these incidents. Subjects and Methods: An epidemiological, retrospective, record-based study was conducted. All self-reported incidents of occupational exposure to blood and OPIM among HCP from all healthcare settings of the Kuwait Ministry of Health during 2010 were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
(35 reference statements)
2
15
2
Order By: Relevance
“…On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [16]. But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [10],Kuwait [17], South Korea [18] and Northern Nigeria [2]. This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques.…”
Section: Discussioncontrasting
confidence: 98%
“…On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [16]. But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [10],Kuwait [17], South Korea [18] and Northern Nigeria [2]. This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques.…”
Section: Discussioncontrasting
confidence: 98%
“…These findings are consistent and similar to the Bosnia/Herzegovinian, Cameroonian, Saudi Arabian studies on risk of occupational exposure conducted [9][12] [13]. On the contrary, higher prevalence of occupational exposure to HIV infection among health care workers than the prevalence found in the current study has been reported by several other researchers in sub-Saharan Africa and other parts of the world [14].But, our findings on prevalence of occupational exposure are above that obtained from similar studies conducted in Poland [8] ,Kuwait [15] , South Korea [16] and Northern Nigeria [17].This difference in prevalence of HIV observed in previous studies and our present study could be as a result of the difference in the study setting, study design and other methodological techniques. The differential in the level of training received by the health care workers in different study settings could also contribute to the variation.…”
Section: Discussioncontrasting
confidence: 75%
“…Most of the NSI cases occurred in the emergency units and the medical surgical units. Omer et al (2015) showed that the NSIs represent the most common mode of exposure in 189 (75.9%) healthcare personnel; [19] while Salmanzadeh et al (2015) showed that the highest frequency of NSIs were observed among medical staff (79.7%). [20] A study by Askarian and Malekmakan (2006) reported that 71.1% (489/688) of the students experienced NSIs which usually occurred in the patient rooms (43.6%); while 82% (401/489) of NSIs were not reported.…”
Section: Discussionmentioning
confidence: 99%